Odpowiedź :
a)[9]³×¹/₂₇÷(_2×3)²=729×¹/₂₇÷36=27÷36=0,75
b)4×2÷2×5⁹=4 ×5⁹
b)4×2÷2×5⁹=4 ×5⁹
a) [(-3)²]³×3⁻³÷[(-2)⁻⁵×3⁷] = (-3)⁶*(⅓)³:[(-½)⁵*2187] = 729*1/27:[1/32*2187] = 27:2187/32 = 27*32/2187 = 864/2187
b) 4×5¹⁰+2×5⁹÷2×5₈ = 2*2*5¹⁰+2*5⁹:2*5⁸ = 2²*5¹⁰+2*5⁹:2*5⁸ =
2³*5¹⁹:2¹*5⁸ = 2²*5¹¹ = 4*5¹¹
c)[(√2+√3)√²]√² = (√2+√3)² = 2+3 = 5
d) (2√²⁻√⁵)√₅⁻√₂ = 2√10-4-5+√10 = 3√10-9
Innego pomysłu na rozwiązanie tego niestety nie mam.
Mam nadzieję, że chociaż trochę pomoglam
b) 4×5¹⁰+2×5⁹÷2×5₈ = 2*2*5¹⁰+2*5⁹:2*5⁸ = 2²*5¹⁰+2*5⁹:2*5⁸ =
2³*5¹⁹:2¹*5⁸ = 2²*5¹¹ = 4*5¹¹
c)[(√2+√3)√²]√² = (√2+√3)² = 2+3 = 5
d) (2√²⁻√⁵)√₅⁻√₂ = 2√10-4-5+√10 = 3√10-9
Innego pomysłu na rozwiązanie tego niestety nie mam.
Mam nadzieję, że chociaż trochę pomoglam